Aprendizagem e trabalho colaborativo na educação a distância - Castro, Rafael Fonseca de (2008)
This Masters dissertation had the intention to contribute to the discussion related to the use of Information and Communication Technology (ICT) and especially of Virtual Digital Technology (VDT) in Education. It adopted the principle that Education, like other parts of society, can also benefit from the sea of possibilities offered by the technologies, which have the potential to be powerful allies in the processes of teaching and learning. More specifically, this dissertation had the aim of investigating the learning processes that are characteristics of E-Learning as well as the influence of collaborative work upon such processes. The work has been based on the theoretical ideas proposed by the Socio-historical-cultural perspective whose main figure is Lev S. Vygotsky. This perspective, sprang from the principles of the dialectical materialism of Marx and Engels, explains that the typical human features are a result of the dialectical relationship between people and their environment. Vygotsky stated that a subject was a real, concrete and social individual whose singularity was a product of his/her belonging to a specific social-historical-cultural group. Based on such conception, this author theorized about the importance of the other for the learning process, idea expressed in the concept of Zone of Proximal Development. Such concept is fundamental for the understanding the importance of collaboration in Education idea further developed by Gordon Wells. The investigation, which had a qualitative and exploratory character, has been based on data collected through semi-structured interviews with six students enrolled in ELearning courses. The content analysis of data produced findings which suggest that: a) learning can happen in E-Learning; b) students can feel motivated in this educational modality; c) group activities are considered important, by the students, for their learning processes; d) the way courses organize the activities proposed to students can influence the occurrence of collaborative work, that may comes to arouse effective learnings, as the studied theory says; e) it is possible to constitute Communities of Inquiry in E-Learning.